Synopsis of the Asian species in the genus Zarcosia Collado & Alonso-Zarazaga, 1996 with new combinations and descriptions of fourteen new species - Gompel, Nicolas (Zootaxa, 2020)
This work represents a provisional inventory of Asian species placed in the genus Zarcosia Collado & Alonso-Zarazaga, 1996. Most of these species had not been reassigned since their original description under now obsolete genera, in spite of the morphological homogeneity of the genus Zarcosia Collado & Alonso-Zarazaga, 1996. The present work includes the following transfers resulting in 34 new combinations: Z. armipes (Fairmaire, 1896), comb. nov.; Z. batuensis (Werner, 1962), comb. nov.; Z. bipartita (Pic, 1901), comb. nov.; Z. capitalis (Pic, 1901), comb. nov.; Z. cephalica (Werner, 1962), comb. nov.; Z. dentatifemur (Pic, 1912), comb. nov.; Z. discoidalis (Pic, 1902), comb. nov.; Z. genjiensis (Pic, 1917), comb. nov.; Z. glaucescens (Champion, 1920), comb. nov.; Z. grandiceps (Pic, 1899), comb. nov.; Z. holosericea (Champion, 1916), comb. nov.; Z. javana (Pic, 1894), comb. nov.; Z. kempi (Blair, 1924), comb. nov.; Z. longithorax (Pic, 1899), comb. nov.; Z. lucifuga (Heberdey, 1931), comb. nov.; Z. luteitarsis (Champion, 1924), comb. nov.; Z. malayana (Werner, 1962), comb. nov.; Zarcosia nathani (Pic, 1943), comb. nov.; Z. nigrofasciata (Pic, 1899), comb. nov.; Z. obscuricornis (Pic, 1927), comb. nov.; Z. palliditarsis (Pic, 1912), comb. nov.; Z. patucki (Champion, 1924), comb. nov.; Z. picina (Fairmaire, 1893), comb. nov.; Z. plumbea (Champion, 1916), comb. nov.; Z. proprior (Pic, 1920), comb. nov.; Z. rubrobasalis (Pic, 1921), comb. nov.; Z. rufotestacea (Pic, 1901), comb. nov.; Z. sellata (Champion, 1916), comb. nov.; Z. sexdentata (Champion, 1924), comb. nov.; Z. subrobusta (Pic, 1943), comb. nov.; Z. subrufa (Champion, 1924), comb. nov.; Z. testaceitarsis (Pic, 1926), comb. nov.; Z. troglodytes (Champion, 1916), comb. nov.; Z. uncifer (Champion, 1916), comb. nov. In addition, based on the study of over 200 Asian specimens, the geographical distribution of each species is outlined. The study of numerous collections lead me to recognize 14 new species, distinguishable, at least by male genitalia, that I describe here: Zarcosia barlayi n. sp., Zarcosia bedosae n. sp., Zarcosia brunnea n. sp., Zarcosia deharvengi n. sp., Zarcosia gerstmeieri n. sp., Zarcosia ilonae n. sp., Zarcosia intermedia n. sp., Zarcosia lemairei n. sp., Zarcosia schawalleri n. sp., Zarcosia sinuata n. sp., Zarcosia spinifemur n. sp. Zarcosia srilankaensis n. sp., Zarcosia sumatrensis n. sp. and Zarcosia weigeli n. sp. Finally, I propose a new synonymy for Hylophilus picinus var. rufescens Pic, 1905 = Zarcosia picina (Fairmaire, 1893), syn. nov. and design two lectotypes, for Xylophilus picinus, Fairmaire, 1893, pres. design. and for Zarcosia subglaber Pic, 1952 pres. design.